Antioxidant biocompatible composite collagen dressing for diabetic wound healing in rat model. Issue 2 (13th March 2021) - Qian, Bei; Li, Jialun; Guo, Ke; Guo, Nengqiang; Zhong, Aimei; Yang, Jie; Wang, Jiecong; Xiao, Peng; Sun, Jiaming; Xiong, Lingyun
Abstract: Associated with persistent oxidative stress, altered inflammatory responses, poor angiogenesis and epithelization, wound healing in diabetic patients is impaired. N-acetylcysteine (NAC) is reported to resist excess reactive oxygen species (ROS) production, prompt angiogenesis and maturation of the epidermis. Studies have revealed that graphene oxide (GO) can regulate cellular behavior and form cross-links with naturally biodegradable polymers such as collagen (COL) to construct composite scaffolds. Here, we reported a COL-based implantable scaffold containing a mixture of GO capable of the sustained delivery of NAC to evaluate the wound healing in diabetic rats. The morphological, physical characteristics, biocompatibility and NAC release profile of the GO-COL-NAC (GCN) scaffold were evaluated in vitro . Wound healing studies were performed on a 20 mm dorsal full-skin defect of streptozotocin (STZ)-induced diabetic rats. The injured skin tissue was removed at the 18th day post-surgery for histological analysis and determination of glutathione peroxidase (GPx), catalase (CAT) and superoxide dismutase (SOD) activity. In diabetic rats, we confirmed that the GCN scaffold presented a beneficial effect in enhancing the wound healing process. Additionally, due to the sustained release of NAC, the scaffold may potentially induce the antioxidant defense system, upregulating the expression levels of the antioxidant enzymes in the wound tissue. The findings revealed that the antioxidant biocompatible composite collagen dressing could not only deliver NAC in situ for ROS inhibition but also promote the wound healing process. This scaffold with valuable therapy potential might enrich the approaches for surgeon in diabetic wound treatment in the future.